Kuwait : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2003)
This 2002 Article IV Consultation highlights that in 2001, overall real growth for Kuwait fell slightly as oil output dropped following OPEC-mandated production cuts. The real non-oil GDP growth decelerated to 0.5 percent from 1 percent in 2000 as the private sector investment remained broadly unchanged. Inflation remained low at less than 2 percent, reflecting little increase in import prices and a modest nominal effective appreciation of the dinar. The macroeconomic position continued to be strong despite a decline in oil exports receipts.